STUDENTS’ ABILITY TO TRANSLATE A SCIENTIFIC DISCOURSE TEXT FROM ENGLISH INTO INDONESIAN - Muhammad Dzikri (Universitas Bung Hatta, 2022)
The purpose of this research was to describe the university students’ ability in applying grammatical adjustment and lexical equivalence to translate a scientific discourse text from English into Indonesian. The design of this research was descriptive. Theresearcher used total sampling technique and the sample was 26 students. The instrument for collecting the data in this research was translation test of scientific discourse text about Biology. To make the test reliable the researcher used inter-rater technique. The result of analysis showed that the test was reliable. It was supported by the fact that the coefficient correlation was 0.93. It was categorized as very high correlation. Then the test was valid in terms of content because it covered the material that students had learnt. The research found that generally, all of the students have been able to translate scientific discourse text. In general 61.54% students got excellent ability and 38.46 % students got good ability. In applying lexical equivalence 84.62% students got excellent ability, 15.38% got good ability. In applying grammatical adjustment 3.85% got excellent ability, 73.08% got good ability, 19.23% got fair ability and 3.85% got poor ability. REFERENCES Abidin, Y., Misbah, B. F. J. M., Putra, A. W., Ertinawati, Y. (2013). Kemahiran Berbahasa Indonesia Untuk Perguruan Tinggi: Buku Pegangan Mata Kuliah Wajib Umum (MKWU) Bahasa Indonesia Kurikulum 2013 di Perguruan Tinggi. Jakarta: Bumi Aksara. Awadalbari, A, M, M. (2015) Translation as an aid to enhance Students’ Writing Skills at University Level, SUST Journal of Humanities. 947 (9) Baryadi, P. (2015). Analisis Wacana. Jurnal Bahan Lokakarya Metode Penelitian Bahasa dan Sastra Indonesia, 2-3. Brown, H., D., & Abeywickrama, P. (2010).Language Assesment: Principle and Classroom Practices. New York: Pearson Education. Fadillah, F. N. (2019). An Analysis of the Third Year Students’ Ability in Translating English Spoof text into Indonesian at the English Literature of Bung Hatta University. Unpublished Thesis. Padang: Bung Hatta University. Fikra, F., Tanjung, F., Refnita, L. (2014). An Analysis of the Third Year Students’ Ability of English Department at Bung Hatta University in Translating “Job Vacancy Text” from English into Indonesian. E-Jurnal Universitas Bung Hatta, 1 (3). Gay, L. R,.Mills, G. E., &Airasian, P (2012). Educational Research book: Competencies for Analysis and Applications (10 ed.). New Jersey: Pearson Education Hatim, B,. & Munday, J. (2004) Translation : An Advanced Resource Book. New York: Routledge Melyani, M., I., Tanjung, F., Ernati. (2014). An Analysis Of Third Year Students’ Ability In Translating English Narrative Text Into Indonesian at Bung Hatta University. E-Jurnal Universitas Bung Hatta, 2 (3). Nababan, M,.Nuraeni, A., & Sumardiono. (2012). Pengembangan Model Penilaian Kualitas Terjemahan. Jurnal Kajian Linguistik dan Sastra, 24, 50-51 Rahayu, D., S., Tanjung, F., Refnita, L. (2017). The Analysis of the Third Year Students’ Ability to Translate Scientific Text from English into Indonesian at English Department of Bung Hatta University. E-Jurnal Universitas Bung Hatta, 3 (6). Ramadhani, F., Tanjung, F., Ernati.(2014). Ananalysis of the Third Year Students’ Ability in Translating The Advertisement on The Newspaper From English into Indonesian At English Department of Bung Hatta University. E-Jurnal Universitas Bung Hatta, 1 (3). Refnita, L. (2018). Educational Research: A Guide for Beginner. Padang: LPPM Universitas Bung Hatta. JurnalUniversitas Bung Hatta Suriadi, A. Roza, W. Harha, K. (2014). An Analysis on the Third Year Students’ Ability of English Department of Bung Hatta University in Translating Analytical Exposition Text From English Into Indonesian. E-Jurnal Universitas Bung Hatta, 3 (3) Thurina, F. (2014). An Analysis of the Ability of the Fourth Year Students in the English Department of Bung Hatta University in Translating an Educational News of Jawa Post Newspaper From Indonesian into English. Unpublished Thesis. Utomo, S., Tanjung, F., Refnita, L. (2013).The Difficulties of the Third Year English Department Students to Translate an Educational News Text from English into Indonesian at Bung Hatta University, E-Jurnal Universitas Bung Hatta, 1-3 (2).